Risk Assessment in the Prevention of Cardiovascular Disease in Low- Resource Settings – Lessons for practitioners in Nigeria - Ofori, Sandra Nnedinma; Odia, Osaretin James (The Nigerian Health Journal, 2015)
Background: Cardiovascular disease prevalence is increasing in low and middle-income countries, which bear around 75-80% of the global burden. Total cardiovascular disease risk assessment is key to prevention. Methods: A search of studies published between 1990 and 2013 was conducted. Medline database, PubMed and World Health organization report sheets were used. Results: The ideal risk prediction tool is one that is derived from the population in which it is to be applied. In the absence of national population based cohort studies in sub- Saharan African countries like Nigeria^ there is no tool that is used consistently. Regardless of which one is adopted by national guidelines, routine consistent use is advocated by various CVD prevention guidelines. Conclusions: In low-resource settings, the consistent use of simple tools like the WHO charts is recommended as the benefit of a standard approach to screening outweighs the risk of missing an opportunity to prevent CVD.